Challenges and strategies used by nurses in an Intensive Care Unit infected by the Coronavirus (Research, Society and Development, 2024)
Objective: To analyze the challenges and strategies used by nurses in an Intensive Care Unit who were infected by coronavirus. Method: Qualitative, exploratory and descriptive study. Data collection took place from November 2021 to January 2022, through semi-structured interviews in an online format with 14 nurses from an Intensive Care Unit who were infected by the virus. The data was subjected to Content Analysis, two categories emerging: Challenges of nurses contaminated by coronavirus and Strategies used by nurses contaminated by coronavirus. Results: The challenges verbalized by the interviewees were: social isolation, return to work and post-illness syndrome. The strategies used were: online contact with family members, well-being practices and therapy. Final Considerations: The experiences of this period were transformative for the study subjects, as in the position of patient, they experienced feelings that had not been experienced before, qualifying the nursing care provided to this type of patient.